HEALTH PROMOTION IN BRAZIL'S PRIMARY ATTENTION: INTEGRATIVE REVIEW (Fiep Bulletin - online, 2016)
Objective: To identify the profile of publications on health promotion in the Brazilian primary care. Method: The research characterized as a descriptive literature review, exploratory type Integrative Review of Literature. To identify articles to write this review, we used the Medical Subject Headings: health promotion, primary health care and Brazil. The search took place in the Virtual Health Library Research Portal between the months of September and October 2015, setting the sample in 15 productions, from the inclusion and exclusion criteria. Results: It found that dominated the 2014 year of publication, four or more authors, available in LILACS, in the Journal of Public Health and Portuguese. The topics covered were educational and low effectiveness in the actions promote health, health promotion programs and encouraging specific actions, National Primary Care Policy and advances and challenges for health promotion. Conclusion: It expected to attract the interest of researchers on the subject, and especially strengthen the need to effect actions promoting health in primary care.
Keywords: Health Services. Primary Health Care. Health Promotion.